A new species of Wrightoporia (Wrightoporiaceae, Basidiomycota) from Sri Lanka - Zhou, Meng; Chen, Jiajia; Yuan, Yuan (Phytotaxa, 2020)
A new resupinate polypore, Wrightoporia srilankensis sp. nov., is described from Sri Lanka. It is characterized by annual resupinate basidiocarps with buff yellow pores, margin and subiculum with rhizomorphs, a dimitic hyphal structure with yellowish crystals on both generative and skeletal hyphae, generative hyphae bearing clamp connections, dextrinoid and cyanophilous skeletal hyphae, the absence of gloeoplerous hyphae and gloeocystidia, and broadly ellipsoid, hyaline, thick-walled, finely asperulate, strongly amyloid, cyanophilous basidiospores measuring 3.8–4.2 × 2.8–3.2 µm. Molecular phylogenetic analyses based on ITS and nLSU rDNA sequences confirmed that W. srilankensis nested in the Wrightoporia clade. W. srilankensis is closely related to Wrightoporia avellanea which, however, lacks cystidioles, and its hyphae are smooth (without crystals).